Ecologia e estrutura trófica do caranguejo aranha Libinia ferreirae (Decapoda: Majoidea) no Litoral sul de São Paulo - Gonçalves, Geslaine Rafaela Lemos (2020)
Symbioses are ubiquitous in the animal kingdom. However, in most cases the role played by each member of the partnership is relatively fixed and it is rare for the same species to show different symbiotic behaviours during ontogeny. In this study, we investigated the relationships between the spider crab Libinia ferreirae its jellyfish host and sea anemones a carapace epibiont. We ask the following questions: How do the food sources used by the crab change between the juvenile and adult phase? How does the symbiotic relationship change when the develops from a juvenile into an adult? Stable isotope analyses (SIMMr package in R) were used to determine the extent to which L. ferreirae juveniles were feeding on medusae hosts versus planktonic prey during the symbiont phase and feeding on their epibionts during the free-living phase. δ13C of L. ferreirae differed between juvenile (associated with the jellyfish) and adult stages (free-living), indicating little isotopic niche overlap between these life phases. SIMMr models using δ13C and δ15N of the crab and their potential food sources suggested that juvenile crab symbionts did not derive any significant nutrition from medusae and relied predominantly from zooplankton prey. As juvenile crab does not have structures to capture zooplankton for feeding, we suggest that the juvenile crab could be kleptoparasites stealing zooplankton food from their host, but more food sources need be tested before confirm the type of the relationship. The nutrition of free-living crab was predominantly derived from fee-living algae and shrimps and not epibionts. Likewise, the epibionts appeared to rely on similar food resources, suggesting a symbiotic relationship more akin mutualism. Thus, the crabs move from a symbiosis where they can act as parasites to one where they act as hosts. These different relationships that L. ferreirae live bring food sources, protection from predators and dispersion for a wider range of environments, increasing the chances of survival. Such flexible approaches to symbioses may be much more common than currently described, particularly in species where the functional roles of individual life stages differ.